National Passive Principles in Illegal Fishing Disputes of Indonesian Citizens in Australian Waters - Imrona, Imrona; Kusuma, Meutia Alfi (Universitas Negeri Semarang, 2023)
Illegal fishing remains a contentious issue globally, often leading to diplomatic tensions and strained relations between neighboring countries. This paper explores the application of national passive principles in the context of illegal fishing disputes involving Indonesian citizens in Australian waters. By examining relevant international laws, bilateral agreements, and case studies, this paper aims to elucidate the legal frameworks and practical implications of national passive principles in resolving such disputes. The analysis highlights the challenges faced by both Indonesia and Australia in enforcing maritime laws, particularly concerning illegal fishing activities. Moreover, it investigates the role of national passive principles, which prioritize the rights and responsibilities of states over their citizens engaged in illegal activities abroad. Through a comparative study of legal approaches and diplomatic strategies employed by both countries, this paper seeks to offer insights into the effectiveness of national passive principles in deterring illegal fishing and promoting cooperation between nations. Furthermore, this paper discusses the socio-economic factors driving illegal fishing activities among Indonesian citizens, including poverty, lack of alternative livelihoods, and inadequate enforcement measures. It also examines the environmental impact of illegal fishing on marine ecosystems and the need for collaborative efforts to combat this transnational issue. In conclusion, this paper underscores the importance of international cooperation, legal compliance, and sustainable resource management in addressing illegal fishing disputes. It advocates for the continued implementation of national passive principles alongside strengthened enforcement mechanisms and community-based initiatives to achieve long-term solutions to illegal fishing in Australian waters.